2009
DOI: 10.1021/ma802192y
|View full text |Cite
|
Sign up to set email alerts
|

Copoly(arylene ether)s Containing Pendant Sulfonic Acid Groups as Proton Exchange Membranes † NRCC Publication No. 50899.

Abstract: /npsi/ctrl?action=rtdoc&an=3538010&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=3538010&lang=frAccess and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 28 publications
0
74
0
Order By: Relevance
“…Our earlier work has shown that pendent phenyl rings attached to electron-donating polymer chain sites can be preferentially sulfonated at the para position, without obvious chain degradation occurring during sulfonation. [39][40][41][42][43] In the present study, the copolymers 2-PAES-60 and 4-PAES-20, having pendent phenyl groups on the electron-withdrawing site of the polymer chain were sulfonated on the para-phenyl position with chlorosulfonic acid to produce PS2-PAES-60 and PS4-PAES-20, respectively ("postsulfonation" is distinguished by PS). On the basis of experimental IEC w values, a 5-fold molar excess of chlorosulfonic acid was necessary for complete sulfonation.…”
Section: Methodsmentioning
confidence: 86%
“…Our earlier work has shown that pendent phenyl rings attached to electron-donating polymer chain sites can be preferentially sulfonated at the para position, without obvious chain degradation occurring during sulfonation. [39][40][41][42][43] In the present study, the copolymers 2-PAES-60 and 4-PAES-20, having pendent phenyl groups on the electron-withdrawing site of the polymer chain were sulfonated on the para-phenyl position with chlorosulfonic acid to produce PS2-PAES-60 and PS4-PAES-20, respectively ("postsulfonation" is distinguished by PS). On the basis of experimental IEC w values, a 5-fold molar excess of chlorosulfonic acid was necessary for complete sulfonation.…”
Section: Methodsmentioning
confidence: 86%
“…The roughness of membrane before treatment showed rougher than that the membrane after treatment. This properties exposing the membrane to higher proton even for shorter times, indicating that this process depends mainly on the total amount of ionomer (proton) deposited to the system during the process treatment [15]. …”
Section: H Nmr Study Resultsmentioning
confidence: 97%
“…This trend can be explained for two reasons: (1) The polymeric main chains will increase in flexibility at elevated temperatures (providing a larger free volume in favor of enhanced ion transport); 30 (2) Faster diffusion and thermal motion of hydroxide ions promote ion conduction at elevated temperatures (overcoming the activation energy for ion transport). 39,40 Of particular note, M-5 exhibited ionic conductivities above 100 mS cm -1 at 80°C: This shows that the alkali anion conductivities of AAEMs can approach the magnitude of H + conduction in PEMs.…”
Section: Hydroxide Conductivitymentioning
confidence: 85%